Projeto e desenvolvimento de fontes auxiliares para transformadores de estado sólido - Kehler, Leandro Becker (2015)
This master thesis presents the development of an auxiliary power supply to provide energy to sensors, gate drivers, instrumentation circuits and control of a three-stage Solid State Transformer (SST). These devices require an insulated power supply of ±15V and 5V. For reason of reliability and modularity, a distributed auxiliary source is proposed. Thus, it is necessary a power supply to provide energy to the low voltage (LV) side and another to the medium voltage (MV) side. With this proposal, the auxiliary power supply does not need to have the same galvanic insulation of the SST, 25kV. However, a local power supply must operate at high voltage levels and, consequently, contain a high step-down voltage gain. Relative to LV side, the most generally used topologies as an auxiliary power supply are discussed. However, these topologies cannot be used at the MV converters, due to the high voltage stress levels involved. A study of topologies used on medium and high voltage and which enable to reach a high step-down voltage gain is realized, and two interesting topologies for this application were found. One of them uses a Flying capacitor converter connected in cascade with a Double-Ended Flyback converter. The Flying capacitor converter lowers the DC bus voltage in a controlled manner to low voltage levels. So the Double-ended Flyback converter operates in LV and provides the insulated outputs to command circuits of SST. The other topology is a unidirectional four-level NPC converter operating as Double-ended Flyback converter. For this case, a modulation strategy that allows the converter to reach a high step-down voltage gain was also proposed. These topologies were evaluated and the one which showed the best result was the four-level Double-ended Flyback converter. This converter was implemented and the experimental results prove to be effective. For the LV side, a Half-bridge LLC resonant converter as auxiliary power supply was used. This converter operates in ZVS and performs the output voltage regulation through the operating frequency variation. The experimental results of this converter are also presented.